Understanding democratic education policy queerly: Toward a queer democratic framework - Leonardi, Bethy; Moses, Michele S. (Education Policy Analysis Archives, 2021)
The aim of this paper is to bring together concepts and commitments from both liberal and queer theories with the purpose of designing an integrated framework for equity-focused education policy analysis and implementation. In essence, we aim to build a conceptual bridge between queer and liberal democratic theories and to develop what we call a “queer democratic framework” for policy analysis and implementation. We use the case of the Fair Accurate Inclusive and Respectful Education Act (FAIR) throughout this paper as an exemplar of how queer policy analysis and implementation change the terms of the policy discussion. We argue that as an example of a policy that comes out of liberal democratic theory, FAIR can only go so far. It is symbolic and positive, but cannot reach emancipatory aims in practice without queer analysis and implementation.